2001
DOI: 10.1046/j.1365-3059.2001.00613.x
|View full text |Cite
|
Sign up to set email alerts
|

Synergism between plant viruses: a mathematical analysis of the epidemiological implications

Abstract: Many virus diseases of plants are caused by a synergistic interaction between viruses within the host plant. Such synergism can induce symptoms more severe than would be caused by additive effects. In a synergistic interaction, the virus titre of both, one, or neither virus may be enhanced and, as a consequence, the rate of disease spread may be affected. An epidemiological model was developed in which transmission and loss rates were attributed to the different virus infection possibilities. Sharing the same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 44 publications
1
35
0
1
Order By: Relevance
“…The study also showed that mixed infection with BICMV and CYMV were more pathogenic than single viral inoculation. Zhang et al, (2000 and2001), had reported that viral interactions and coinfection with two independent unrelated viruses resulted in a much more serious disease than either virus in a single infection. This situation is often referred to as synergism ( ).…”
Section: Discussionmentioning
confidence: 99%
“…The study also showed that mixed infection with BICMV and CYMV were more pathogenic than single viral inoculation. Zhang et al, (2000 and2001), had reported that viral interactions and coinfection with two independent unrelated viruses resulted in a much more serious disease than either virus in a single infection. This situation is often referred to as synergism ( ).…”
Section: Discussionmentioning
confidence: 99%
“…To date, there have been very few attempts in the literature to create a mathematical model of HBV-HDV dynamics. The earlier models of Zhang et al [6,7] are related in that they consider the competing dynamics of two viruses in a host plant population. The first known HBV-HDV model was proposed by Sousa and Cunha [8] and investigated numerically.…”
Section: Introductionmentioning
confidence: 99%
“…In the synergistic situations, either virus titre or the movement or both can be enhanced [35,43]. Breakdown of resistance by a co-infection with an unrelated virus is also an indication of a synergistic interaction [6,22,28,30].…”
Section: Introductionmentioning
confidence: 99%